PENGARUH KEPUASAN KERJA KARYAWAN TERHADAP TURNOVER INTENTION PT PRODIA WIDYAHUSADA Tbk, WILAYAH VI DIVISI PELAYANAN - Candra, Virlia Alvionita; Kusmaningtyas, Amiartuti (JEM17: Jurnal Ekonomi Manajemen, 2020)
This study aims to analyze the influence of job satisfaction employee to turnover intention PT. Prodia Widyahusada Tbk, Region VI divisi customer service. This research uses qualitative approach with partial least squares (PLS) based on empirical theory between variables in this research, then data collected by questionnaire instrument. Sampling method used in this research is purposive sampling that is all employees of PT. Prodia Widyahusada Tbk, Region VI divisi customer service who have working period over one year as many as 132 employees all of population. The results of this study indicate that Job satisfavction have a positive effect on turnover intention.Kata Kunci : turnover, intention, jobs, satisfaction.